The Mechanism Underlying the ncRNA Dysregulation Pattern in Hepatocellular Carcinoma and Its Tumor Microenvironment - Xue, Chen; Gu, Xinyu; Bao, Zhengyi; Su, Yuanshuai; Lu, Juan; Li, Lanjuan (Frontiers in Immunology, 2022)
HCC is one of the most common malignant tumors and has an extremely poor prognosis. Accumulating studies have shown that noncoding RNA (ncRNA) plays an important role in hepatocellular carcinoma (HCC) development. However, the details of the related mechanisms remain unclear. The heterogeneity of the tumor microenvironment (TME) calls for ample research with deep molecular characterization, with the hope of developing novel biomarkers to improve prognosis, diagnosis and treatment. ncRNAs, particularly microRNAs (miRNAs), long noncoding RNAs (lncRNAs), and circular RNAs (circRNAs), have been found to be correlated with HCC neogenesis and progression. In this review, we summarized the aberrant epigenetic and genetic alterations caused by dysregulated ncRNAs and the functional mechanism of classical ncRNAs in the regulation of gene expression. In addition, we focused on the role of ncRNAs in the TME in the regulation of tumor cell proliferation, invasion, migration, immune cell infiltration and functional activation. This may provide a foundation for the development of promising potential prognostic/predictive biomarkers and novel therapies for HCC patients.